2019
DOI: 10.3390/rs11192209
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Phenotyping of Northern Leaf Blight in UAV Images Using Deep Learning

Abstract: Plant disease poses a serious threat to global food security. Accurate, high-throughput methods of quantifying disease are needed by breeders to better develop resistant plant varieties and by researchers to better understand the mechanisms of plant resistance and pathogen virulence. Northern leaf blight (NLB) is a serious disease affecting maize and is responsible for significant yield losses. A Mask R-CNN model was trained to segment NLB disease lesions in unmanned aerial vehicle (UAV) images. The trained mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 41 publications
(46 reference statements)
3
51
0
1
Order By: Relevance
“…Since no prior studies have attempted to map VFFs using automated methods, we are not able to relate our findings to any prior studies that have explored this specific task; however, our findings do reinforce those of Tier et al [6] and Behrens et al [48], which note the value of CNNs for extracting features from digital terrain data. More broadly, this study supports prior findings that CNNs in general and Mask R-CNN specifically are of great value for mapping features with a unique spatial, contextual, or textural signature and that may not be spectrally separable from other classes or features [51,52,84,85].…”
Section: Study Findingssupporting
confidence: 87%
See 2 more Smart Citations
“…Since no prior studies have attempted to map VFFs using automated methods, we are not able to relate our findings to any prior studies that have explored this specific task; however, our findings do reinforce those of Tier et al [6] and Behrens et al [48], which note the value of CNNs for extracting features from digital terrain data. More broadly, this study supports prior findings that CNNs in general and Mask R-CNN specifically are of great value for mapping features with a unique spatial, contextual, or textural signature and that may not be spectrally separable from other classes or features [51,52,84,85].…”
Section: Study Findingssupporting
confidence: 87%
“…Zhao et al [37] found that Mask R-CNN outperformed UNet for pomegranate tree canopy segmentation. Stewart et al [52] used the method to detect lesions on maize plants from northern leaf blight using unmanned aerial vehicle (UAV) data. Given the small number of studies that have applied this algorithm to remotely sensed data, there is a need for further exploration of this algorithm within the discipline.…”
Section: Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning (DL) algorithms have been successfully applied in various aspects in remote sensing and have contributed to domains such as image classification, object auto-detection, image fusion, and registration [ 74 ]. The supervised DL model commonly requires a greater number of training data and it has more layers and depth than ML [ 75 ]. DL can be used in monitoring the growth conditions of maize and yield predictions as it can obtain higher precision [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The semantic segmentation networks based on CNNs are widely applied in the recognition of buildings [38][39][40][41], the extraction of cadastral boundaries [42] and the land use or land cover change [43,44]. The applications are also expanded to the recognition of the agricultural plants [45], pests and diseases [46,47], especially the Refs. [48] introduced the attention mechanism to realize a better segmentation by inhibiting the low-level features noise throughout the high-level features.…”
Section: Semantic Segmentationmentioning
confidence: 99%